2013
DOI: 10.5713/ajas.2013.13018
|View full text |Cite
|
Sign up to set email alerts
|

Effects of <italic>CSN1S2</italic> Genotypes on Economic Traits in Chinese Dairy Goats

Abstract: The aim of this study was to investigate allele frequencies at the CSN1S2 locus in two Chinese dairy goat breeds and the effects of its variation on dairy goat economic traits. Seven hundred and eight goats from Xinong Saanen (XS, n = 268) and Guanzhong (GZ, N = 440) breeds were selected. The milk samples of 268 XS goats were collected during the middle of lactation, body size parameters (708 goats) and daily milk yield (202 goats) were registered. The RFLP (restriction fragment length polymorphism) and SSCP (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In fact, significant differences were found between genotypes of the goat, sheep, and cattle CSN1S2 locus in relation to milk protein and casein content (Ramunno et al, 2001b ; Noce et al, 2016 ; Ardicli et al, 2018 ). Besides, CSN1S2 genotypes were significantly associated with milk and/or fat yield in goat and sheep (Wessels et al, 2004 ; Lan et al, 2005 ; Yue et al, 2013 ; Vacca et al, 2018 ). For years, the interest of several research groups also focused on the study of connection between milk fat and fatty acid composition and the different milk protein polymorphisms and/or genetic polymorphisms of casein-encoding genes (Bobe et al, 1999 , 2004 ; Chilliard et al, 2006 ; Cebo et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, significant differences were found between genotypes of the goat, sheep, and cattle CSN1S2 locus in relation to milk protein and casein content (Ramunno et al, 2001b ; Noce et al, 2016 ; Ardicli et al, 2018 ). Besides, CSN1S2 genotypes were significantly associated with milk and/or fat yield in goat and sheep (Wessels et al, 2004 ; Lan et al, 2005 ; Yue et al, 2013 ; Vacca et al, 2018 ). For years, the interest of several research groups also focused on the study of connection between milk fat and fatty acid composition and the different milk protein polymorphisms and/or genetic polymorphisms of casein-encoding genes (Bobe et al, 1999 , 2004 ; Chilliard et al, 2006 ; Cebo et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…MY is a polygenic quantitative trait, of high economic and productive importance, and more studies are needed to better understand the biological mechanisms that regulate this type of productive trait. The association of CSN1S2 gene variants with milk fat and total solid concentration has been revealed in Chinese goats (Yue 2013 [ 46 ]), with daily milk yield and milk coagulation parameters in Sarda goats [ 47 ] and milk protein and casein contents in sheep [ 41 ]; no association between CSN2 and CSN1S2 genes and milk protein or dry matter contents were found in Murciano Granadina goats [ 48 ]. The CSN1S2 gene was associated with Somatic Cell Score (SCS) in the present study, another critical parameter, considered an indirect indicator of milk hygienic quality, important in the physiology of lactation in goats [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…CSN1S2* A is considered the ancestor variant for goat according to the evolutionary path from sheep and cattle ( Sacchi et al, 2005 ). This variant is common with a frequency of ≥0.70 in distinct Saanen goats, most Italian, German and Indian goats, Dwarf goats from Nigeria, and Nubian goats from Sudan ( Supplementary Table S4 ) ( Boulanger et al, 1984 ; Bouniol et al, 1994 ; Ramunno et al, 2001b ; Erhardt et al, 2002 ; Marletta et al, 2004 ; Chiatti et al, 2005 ; Marletta et al, 2005 ; Caroli et al, 2007 ; Chessa et al, 2007 ; Kupper et al, 2010 ; Rout et al, 2010 ; Yue et al, 2013 ).…”
Section: Csn1s2mentioning
confidence: 99%
“…Interestingly, the variants CSN1S2 *A, CSN1S2 *C, and CSN1S2 *F were associated with a high amount of α-S2-casein in milk and produced 2.5 g/l per allele ( Boulanger et al, 1984 ; Bouniol et al, 1994 ; Ramunno et al, 2001a ). In Chinese dairy goats, animals carrying the CSN1S2 *FF genotype have higher milk fat and total solids content than CSN1S2 *AA and CSN1S2 *AF genotypes, but do not have lower milk yield ( Yue et al, 2013 ). However, Lan et al (2005) found significant lower milk yield of Xinong Saanen goats carrying the CSN1S2 *FF genotypes compared to other genotypes.…”
Section: Csn1s2mentioning
confidence: 99%